Pengaruh Pursed Lips Breathing Terhadap Status Peningkatan Oksigenasi Perifer Dan Fungsi Ventilasi Paru Pada Pasien PPOK: A Literature Review - Putra, Satria Hanggara; Arafat, Rosyidah; Syam, Yuliana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
AbstractIntroduction :Respiratory disease is the enhancement problem in a world that really needs a solution. Objectives: The purpose of this literature was conducted to evaluate the effect of Pursed Lips Breathing on Peripheral Oxygenation and Lung Ventilation Function.Methods: Relevant studies were searched for in 4 data bases Pubmed, Willey, Science direct and Google Scholar, publication dates 5 years. the collected keywords were â€œPursed Lips Breathingâ€, â€œchronic obstructive pulmonary diseaseâ€, and â€œoxygen saturationâ€. The search results for those keywords were 6 research articles in Pubmed, 13 research articles in Willey, 6 research articles in ScienceDirect, and 33 research articles in Google Scholar. Only 5 studies were relevant to this review.Results: Based on the articles that have been obtained Pursed Lips Breathing is effective in increasing ventilation and Peripheral oxygenation and effective in increasing lung activity for the respiration process. As for the monitoring criteria for the effectiveness of respiration status by looking at the FEV1 and Spo2 indicatorConclusion: The pursed lips breathing intervention is carried out continuously to the patient every day to get optimal results for the respiration process.Keyword: pursed lips breathing, Peripheral oxygenation, Lung Ventilation Function